Climate change pushes an economic insect to the brink of extinction: A case study for Cyamophila astragalicola in Iran. (18th November 2021) - Ghasemi, Saeid; Malekian, Mansoureh; Tarkesh, Mostafa
Abstract: Climate change is one of the main drivers of biodiversity decline worldwide, through shifting or shrinking habitats of species. Predicting the distribution of suitable habitats for species under climate change is essential for conservation planning. Cyamophila astragalicola is a specialist psyllid dependent on a spiny shrub, endemic to Zagros Mountains of Iran. The current study represents a modeling approach for lesser‐known small invertebrates to assess their threat status. Ecological niche modeling was used to assess current suitable habitats of C . astragalicola, to develop model‐based predictions of its habitat suitability under different climatic scenarios, and to assess the extinction risk of the species based on IUCN Red List criteria. Results revealed a sharp decline in suitable habitats (97.26% and 99.8% for the years 2050 and 2070, respectively) under the scenario of RCP 8.5. Further, under the two RCP scenarios, C . astragalicola was classified as IUCN Threat 2. A shift toward higher altitudes with lower temperature and higher precipitation was predicted. Results of modeling are based on abiotic factors only. Human interactions are not modeled; hence, the status of the species may be even more dramatic than the models may reveal. Generally, the results of this study indicate the high sensitivity of C . astragalicola to global warming. The narrow distribution range of the species coupled with the low dispersal ability can increase the risk of extinction. Ecological, economic, and social risks associated with the extinction need to be further evaluated to formulate future management policies. Abstract : The current study represents a modeling approach for a lesser‐known insect ( Cyamophila astragalicola ) to assess its current suitable habitats, predict its habitat suitability under different climatic scenarios, and explore the extinction risk of the species. Our results revealed a sharp decline in the suitable habitats and the high sensitivity of C . astragalicola to global warming. The narrow distribution range of the species coupled with the low dispersal ability of this insect can increase the risk of extinction.